Molecular characterization of malaysian newcastle disease virus (NDV) isolates and efficacy study of carboxymethyl sago starch-acid hydrogel formulated NDV vaccine in chickens - Mahamud, Siti Nor Azizah (2021)
Newcastle Disease (ND) is one of the most devastating diseases of poultry affecting both financial loss and protein availability worldwide. Different genotypes of Newcastle Disease Virus (NDV) have been identified in various bird species and control strategies have been implemented at the farm level including the use of NDV vaccines derived from genotype I and II developed decades ago. However, studies on the detection of NDV isolated from wild birds in Malaysia are lacking. In this study, 6 NDV isolates were identified from the diagnostic samples of commercial chickens and sampling of wild birds and non-poultry birds and further characterized by sequencing of the F gene. Nucleotide sequence analysis of F gene (535bp) was confirmed all 6 isolates are clustered as NDV genotype VIIi, under the recent classification as genotype VII.2 with velogenic properties of multiple basic amino acid residues 112RRQKRF117. Among them, isolate UPM/NDV/IBS362/2016 was identified as velogenic NDV subgenotype VII.2/VIIi with intracerebral pathogenicity index (ICPI) of 1.7 and mean death time (MDT) of 58.4 hours, to be use as challenge virus for vaccine efficacy study. The efficacy of mIBS025 vaccine formulated in standard and carboxymethyl sago starch acid hydrogel (CMSS-AH) as vaccine stabilizers were compared in SPF chickens vaccinated via the eye drop (ED) and drinking water (DW). Storage of virus formulated in standard and CMSS vaccine stabilizer as a freeze-dried vaccine at 27℃ for 10 days did not significantly reduce the respective virus titers, which was retained at 108.56EID50/0.1mL. Chickens vaccinated with CMSS-AH mIBS025 ED (Group 2) developed the earliest and highest HI NDV antibody titer (8log2) followed by standard mIBS025 ED (Group 3) (7log2), both conferred complete protection and drastically reduced virus shedding. On the contrary, chickens vaccinated with standard mIBS025 DW (Group 5) and CMSS-AH mIBS025 DW (Group 4) developed low HI NDV antibody titers of 4log2 and 3log2, respectively, conferred only 50% and 60% protection and continuously shed the virulent virus via oropharyngeal and cloacal routes until the end of the study at 14 dpc.